Expectant management versus IUI in unexplained subfertility and a poor pregnancy prognosis (EXIUI study): a randomized controlled trial. Issue 12 (4th November 2022) - Wessel, J A; Mochtar, M H; Besselink, D E; Betjes, H; de Bruin, J P; Cantineau, A E P; Groenewoud, E R; Hooker, A B; Lambalk, C B; Kwee, J; Kaaijk, E M; Louwé, L A; et al.
Abstract: STUDY QUESTION: For couples with unexplained subfertility and a poor prognosis for natural conception, is 6 months expectant management (EM) inferior to IUI with ovarian stimulation (IUI-OS), in terms of live births? SUMMARY ANSWER: In couples with unexplained subfertility and a poor prognosis for natural conception, 6 months of EM is inferior compared to IUI-OS in terms of live births. WHAT IS KNOWN ALREADY: Couples with unexplained subfertility and a poor prognosis are often treated with IUI-OS. In couples with unexplained subfertility and a relatively good prognosis for natural conception (>30% in 12 months), IUI-OS does not increase the live birth rate as compared to 6 months of EM. However, in couples with a poor prognosis for natural conception (<30% in 12 months), the effectiveness of IUI-OS is uncertain. STUDY DESIGN, SIZE, DURATION: We performed a non-inferiority multicentre randomized controlled trial within the infrastructure of the Dutch Consortium for Healthcare Evaluation and Research in Obstetrics and Gynaecology. We intended to include 1091 couples within 3 years. The couples were allocated in a 1:1 ratio to 6 months EM or 6 months IUI-OS with either clomiphene citrate or gonadotrophins. PARTICIPANTS/MATERIALS, SETTING, METHODS: We studied heterosexual couples with unexplained subfertility and a poor prognosis for natural conception (<30% in 12 months). The primary outcome was ongoing pregnancy leading to a live birth. Non-inferiority would be shown if the lower limit of the one-sided 90% risk difference (RD) CI was less than minus 7% compared to an expected live birth rate of 30% following IUI-OS. We calculated RD, relative risks (RRs) with 90% CI and a corresponding hazard rate for live birth over time based on intention-to-treat and per-protocol (PP) analysis. MAIN RESULTS AND THE ROLE OF CHANCE: Between October 2016 and September 2020, we allocated 92 couples to EM and 86 to IUI-OS. The trial was halted pre-maturely owing to slow inclusion. Mean female age was 34 years, median duration of subfertility was 21 months. Couples allocated to EM had a lower live birth rate than couples allocated to IUI-OS (12/92 (13%) in the EM group versus 28/86 (33%) in the IUI-OS group; RR 0.40 90% CI 0.24 to 0.67). This corresponds to an absolute RD of minus 20%; 90% CI: −30% to −9%. The hazard ratio for live birth over time was 0.36 (95% CI 0.18 to 0.70). In the PP analysis, live births rates were 8 of 70 women (11%) in the EM group versus 26 of 73 women (36%) in the IUI-OS group (RR 0.32, 90% CI 0.18 to 0.59; RD −24%, 90% CI −36% to −13%) in line with inferiority of EM. LIMITATIONS, REASONS FOR CAUTION: Our trial did not reach the planned sample size, therefore the results are limited by the number of participants. WIDER IMPLICATIONS OF THE FINDINGS: This study confirms the results of a previous trial that in couples with unexplained subfertility and a poor prognosis for natural conception, EM is inferior to IUI-OS. STUDY FUNDING/COMPETING INTEREST(S): The trial was supported by a grant of the SEENEZ healthcare initiative. The subsidizing parties were The Dutch Organisation for Health Research and Development (ZonMW 837004023, www.zonmw.nl ) and the umbrella organization of 10 health insurers in The Netherlands. E.R.G. receives personal fees from Titus Health care outside the submitted work. M.G. declares unrestricted research and educational grants from Guerbet, Merck and Ferring not related to the presented work, paid to their institution VU medical centre. A.B.H. reports receiving travel and speakers fees from Nordic Pharma and Merck and he is member of the Nordic Pharma ANGEL group and of the Safety Monitoring Board of Womed. C.B.L. reports speakers fee from Inmed and Yingming, and his department receives research grants from Ferring, Merck and Guerbet paid to VU medical centre. B.W.J.M. is supported by a NHMRC Investigator grant (GNT1176437) and reports consultancy for ObsEva and Merck. M.v.W. received a grant from the Netherlands Organisation for Health Research and Development ZonMW (80-8520098-91072). F.M. received two grants from the Netherlands Organisation for Health Research and Development ZonMW (NTR 5599 and NTR 6590). The other authors report no competing interest. TRIAL REGISTRATION NUMBER: Dutch Trial register NL5455 (NTR5599) TRIAL REGISTRATION DATE: 18 December 2015 DATE OF FIRST PATIENT'S ENROLMENT: 26 January 2017